Locating the Sharīʿa : Legal Fluidity in Theory, History and Practice - Siddiqui, Sohaira (Studies in Islamic Law and Society, 2019)
The study of the sharīʿa has enjoyed a renaissance in the last two decades and it will continue to attract interdisciplinary attention given the ongoing social, political and religious developments throughout the Muslim world. With such a variety of debates, and a corresponding multitude of theoretical methods, students and non-scholars are often overwhelmed by the complexity of the field. Even experts will often need to consult multiple sources to understand these new voices and provide accessible answers to specialist and non-specialist audiences alike. This volume is intended for both the novice and expert as a companion to understanding the evolution of the field of Islamic law, the current work that is shaping this field, and the new directions the sharīʿa will take in the twenty-first/fifteenth century. Contributors are Khaled Abou El Fadl, Asma Afsaruddin Ahmad Ahmad, Sarah Albrecht, Ovamir Anjum, Dale Correa, Robert Gleave, Sohail Hanif, Rami Koujah, Marion Katz, Asifa Quraishi-Landes, David Warren and Salman Younas.